The Use of Web 2.0 as Supplementary Tools to Assist Students’ Writing Activity - Zuraina, Ali; Nabila, Abdul Malek; Noor Azlinda, Zainal Abidin; Noraisah Nurul Fatwa, Mohd Razali (Universiti Malaysia Pahang, 2018)
The study investigates the use of Web 2.0 in assisting tertiary students in their writing. Four (4) types of Web 2.0 tools namely Edmodo, YouTube, Prezi and Padlet were employed to assist students in writing essays. The objectives of this research are to identify the significant difference in students’ scores between pre-test and post-test in essay writing using Edmodo as well as to explore students’ opinions on the use of YouTube, Prezi and Padlet in assisting them to prepare their writing task. The study uses mixed-method research design where quantitative data were gathered through student performance in a pretest and posttest of a writing test. For qualitative data, students’ responses pertaining to their perceptions of using YouTube, Prezi and Padlet were collected from their remarks made in ‘Type a reply’ in Edmodo. The results showed that there was a significant increase in students’ pre and post writing tests while students demonstrated positive perceptions in the use YouTube, Prezi and Padlet. The students also demonstrated positive remarks in the use YouTube, Prezi and Padlet.The study implies that the Web 2.0 tools namely Edmodo, YouTube, Padlet and Prezi employed in the study can be sources or tools for teaching and learning writing via online.